Neglected SCFE Treated with Modified Dunn Procedure: A Case Series - Luthfi Walikram; Jefryan Sofyan; Iman Dwi Winanto (Universitas Muhammadiyah Palu, 2025)
Introduction: Slipped Capital Femoral Epiphysis (SCFE) is a condition of the proximal femoral physis that causes metaphyseal displacement that can lead to femoroacetabular impingement and premature osteoarthritis. The management of SCFE so far had significant complications of avascular necrosis so that the Modified Dunn procedure was developed to allow the visual control of the epiphyseal vascular blood supply. Cases Description: We report 2 cases of SCFE in two 14-year-old males who had previous trauma and then underwent open epiphyseal reduction and fixation with modified Dunn procedure. Postoperative evaluation showed there were no cases of avascular necrosis. In addition, the anatomy of the femoral epiphysis was successfully restored, as indicated by a residual slip angle ranging from 4° to 8°, which was considered minimal and not clinically significant. Discussion: The modified Dunn procedure with a retinacular soft tissue flap approach provides the opportunity to perform anatomical reduction of the displaced femoral epiphysis while allowing visual monitoring of femoral head perfusion through the retinacular tissue. When performed by an experienced operator and with careful and precise surgical technique, this procedure has been shown to produce favorable outcomes, both in terms of low AVN rates, functional improvement, and prevention of osteoarthritis progression. Conclusion: These findings suggest that the modified Dunn technique may be an effective and safe option in the management of SCFE, especially in patients with moderate to severe degrees of slippage. With this approach, not only joint stability can be maintained, but also the anatomical shape of the femoral head can be restored as close to normal as possible.